2019
DOI: 10.1016/j.jjcc.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

A decline in activities of daily living due to acute heart failure is an independent risk factor of hospitalization for heart failure and mortality

Abstract: Background: Although activities of daily living (ADL) are recognized as being pertinent in averting relevant readmission of heart failure (HF) and mortality, little research has been conducted to assess a correlation between a decline in ADL and outcomes in HF patients. Methods: The Kitakawachi Clinical Background and Outcome of Heart Failure Registry is a prospective, multicenter, community-based cohort of HF patients. We categorized the patients into four types of ADL: independent outdoor walking, independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 28 publications
(34 reference statements)
2
45
1
Order By: Relevance
“…Therefore, it is important to identify predictors of ADL decline during hospitalization in patients with HF. It has been demonstrated in elderly patients and patients with HF that age and the nutritional index are associated with ADL decline during hospitalization [33] [34]. Our present study involving elderly patients with HF has shown that the ROAG score serves as a good predictor of changes in ADL, and its predictive ability is comparable to age, nutritional indices, and various other parameters.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Therefore, it is important to identify predictors of ADL decline during hospitalization in patients with HF. It has been demonstrated in elderly patients and patients with HF that age and the nutritional index are associated with ADL decline during hospitalization [33] [34]. Our present study involving elderly patients with HF has shown that the ROAG score serves as a good predictor of changes in ADL, and its predictive ability is comparable to age, nutritional indices, and various other parameters.…”
Section: Discussionsupporting
confidence: 60%
“…We have previously demonstrated that hospitalization for HF was signi cantly correlated with decreased BI as an assessment of ADL, and a decreased BI during hospitalization was associated with worse clinical outcomes [8]. It has also been reported that a decline in ADL due to acute HF is an independent risk factor of hospitalization for HF and mortality [33]. Therefore, it is important to identify predictors of ADL decline during hospitalization in patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed the BI score to be a prognostic predictor of heart failure 18 and stroke. 19 A recent study showed that the BI at discharge may be related to one-year mortality of ACS patients >85 years old undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between a decline in activities of daily living (ADL) due to readmission for heart failure (HF) and outcomes among patients with HF was unclear. Recently, we read with great interest the study by Takabayashi et al [1]. The authors performed a prospective, multicenter, community-based cohort study to investigate the association between the ADL and the clinical outcome in HF patients, with the incidence of hospitalization for HF and mortality during the follow-up as primary outcomes.…”
mentioning
confidence: 99%